Examination of 1,2,4-triazole nucleus. An integrated approach to the search for biologically active substances - Kaplaushenko, A. G.; Sameliuk, Yu. H.; Frolova, Yu. S.; Ihnatova, T. V.; Каплаушенко, Андрій Григорович; Самелюк, Юрій Геннадійович; Фролова, Юлія Сергіївна (Sherman Oaks, California : GS publishing service, 2021)
Every day, the modern pharmaceutical industry enters new drugs and dosage forms into the world register. Among the many new drugs, a small number of basic molecules can be noted. Modification of such molecules leads to a change and increase in biological action as well as to a change in toxicity. One such molecule is 1,2,4-triazole. The heterocycle attracts attention due to its excellent biological action on low toxicity. First of all, derivatives of this heterocycle are considered to be powerful antifungal and antimicrobial agents. However, other types of biological action are becoming more common. For example, in medical practice found drugs “Letrozole” and “Anastrazole” as effective antitumor drugs. To achieve this purpose, ZSMU scientists1 select a matrix based on the nucleus of 1,2,4-triazole at first. For this goal the literary base is worked out at the beginning. The viability of the molecule is then confirmed by computer screening using PASS-online programs and acute toxicity using GUSAR-online. Thus, scientists have selected and synthesized more than 700 new, previously undescribed compounds derived from 1,2,4-triazole.
Каплаушенко А. Г. - ORCID ID: 0000-0003-3704-5539; Самелюк Ю. Г. - ORCID ID: 0000-0001-8675-5081; Фролова Ю. С. - ORCID ID: 0000-0002-3995-5088